Peran Trehalose Metabolisme Sepanjang Masa Kehidupan Tanaman - Prapti Sedijani (Jurnal Biologi Tropis, 2014)
AbstractTrehalose/T6P has important role at entire plant stage of life starting from embryonicstage, vegetative growth, generative growth and senescence. The roles include celldevision, cell shape, plant architectecture, and plant responses to biotic and abiotic stress.Syncrunizing between energy demand and energy availability is the main mode of theroles through reprogramming of gene expression responsible for anabolism and/orcatabolism processes depending on given situation including biotic and abiotic stress.Moreover, proteins of trehalose metabolism are suggested to affect enzyme activity oftarget proteins. SnRK1 and bZIP11 involve in all those modes. Understanding crusialroles of trehalose metabolism in plant therefore is necessary in order to get benefit fromthis pathway for agricultural issue.AbstrakTrehalose/T6P berperan penting bagi tahapan kehidupan tanaman dari tahap embryo,pertumbuahn vegetatif, pertumbuhan generatif, hingga sanesensi. Peran molekul tersebutberpengaruh pada pembelahan sel, bentuk sel, arsitektur tanaman dan respon tumbuhanterhadap stres biotik dan abiotik. Pengintegrasian antara kebutuhan dan ketersediaanenergi merupakan modus utama dalam peran tersebut melalui pemrograman ekspresi genyang bertanggung jawab terhadap proses anabolisme dan atau katabolisme sesuai dengansituasi tertentu termasuk dalam kondisi stres biotic dan abiotik. Selain itu, protein-proteindalam lintasan metabolisme trehalose ini juga diduga mempengaruhi aktivitas enzimenzimtarget. Peran krusial metabolisme trehalose, manusia dapat memanfaatkan lintasanini untuk kepentingan pertanian.